The relatıonshıp between work related support and work engagement - Güvenç, Sinem (My University, 2012)
Günümüzde hem yazında hem de İnsan Kaynakları pratiğinde çalışanların örgüte ve işe karşı olan olumlu tutum ve davranışların ortaya çıkarılması ve devamlılığının sağlanması önemli yer tutmaktadır. Zira bu tarz tutum ve davranışlara sahip olan çalışanlar çalıştıkları kurum için de birer değer olacaklardır. Kuruma bağlılıkları ve performans çıktıları gibi somut sonuçlarının yanı sıra çalışanın hayatına refah ve hayat kalitesi anlamında de pek çok şey katacaktır. Bu çalışmanın amacı bireyin işine yönelik Dinçlik, Yoğunlaşma ve Adanmışlık boyutlarını içeren olumlu bir ruh hali olan Çalışmaya Tutkunluk ve İşe Yönelik Destek başlığı altında ele alacağımız Kurum Desteği, Yönetici Desteği ve İş Arkadaşı Desteği kavramları arasındaki ilişkiyi araştırmaktır. Yazındaki farklı pek çok araştırmada söz konusu İşe Yönelik Destek türleri ve Çalışmaya Tutkunluk ilişkisi ayrı ayrı ele alınmış ve aralarında pozitif ve anlamlı ilişkiler gözlemlenmiştir. Çalışmamız, bu üç destek türünün hepsini birden ele alarak Çalışmaya Tutkunluk ile olan ilişkilerini araştırması bakımından yazındaki diğer araştırmalardan ayrılmaktadır. Çalışma İstanbul’da farklı sektörlerde çalışan 205 katılımcı üzerinde yapılmıştır. Analizler sonucunda İşe yönelik Destek ve Çalışmaya Tutkunluk arasındaki ilişki kısmen desteklenmiştir. Sadece Kurum Desteği ve Yönetici Desteğinin Çalışmaya Tutkunluk üzerinde pozitif ve anlamlı katkılarının olduğu bulunmuştur. Öte yandan İş Arkadaşı Desteğinin Çalışmaya Tutkunluk üzerinde anlamlı bir katkısı olmadığı ortaya çıkmıştır. alışmaya Tutkunluk, İşe Yönelik Destek, Kurum Desteği, Yönetici Desteği, İş Arkadaşı Desteği

In today’s world it is important to discover and maintain workers’ positive attitudes and behavior towards their organizations and their works for both the scientific literature and HR practices; because employees with such attitudes and behaviors will become very valuable for their organizations. They will make many contributions to the workers welfare and life quality among their dedication to the organization and performance outputs. The aim of this paper is to research the relationship between Work Engagement –which can be described as a positive state of mind of the individual that encompasses vigor, absorption and dedication dimensions- and Organizational Support, Supervisor Support and Co-worker Support, which in turn is mentioned under the Work Related Support title. Many different studies in literature have taken into consideration the relationship between the above mentioned Work Related Support types and the Work Engagement notion. In these studies only one or two support types are researched along with other variables such as autonomy or skill variety. In these studies a positive and significant relationship has been observed in many times. However this research paper is different from these studies as it studies the three support types together and their relationship with the Work Engagement. The study is conducted on 205 participants from different sectors in Istanbul. It has been found that there’s a partial relationship between Work Related Support and Work Engagement. A positive and significant relationship has only been found between Work Engagement and Organizational Support and also Supervisor Support. On the other hand, no significant relationship has been found between Co-worker Support and Work Engagement. Key Words: Work Engagement, Work Related Support, Organizational Support, Supervisor Support, Co-Worker Support
Keywords: İş Tatmini; Örgütsel Davranış